Acidic urine is associated with poor prognosis in patients with bladder cancer undergoing radical cystectomy - Han, Jang Hee; Jeong, Seung-hwan; Yuk, Hyeong Dong; Jeong, Chang Wook; Kwak, Cheol; Ku, Ja Hyeon (Frontiers in Oncology, 2022)
Purpose To assess the prognostic value of acidic urine (low urine pH) in patients with bladder cancer undergoing radical cystectomy. Materials and methods We reviewed patients enrolled in the Seoul National University Prospectively Enrolled Registry for Urothelial Cancer-Cystectomy (SUPER-UC-Cx) who underwent radical cystectomy for bladder cancer between March 2016 and December 2020 at the Seoul National University Hospital. During this period, 368 patients were registered in our database. To eliminate confounding factors, we excluded patients diagnosed with non-urothelial cancer and end-stage renal disease. Results A total of 351 patients with a mean age of 69.8 ± 10.5 years and median follow-up of 16.0 months were eligible for the analysis. The mean preoperative urine pH was 6.0. The patients were divided into low (pH ≤ 5.5) and high (pH≥6.0) urine pH groups for comparison. All clinicopathological features, including the tumor size, grade, and stage were comparable between the low and high urine pH groups. A Cox regression analysis was performed to assess the independent effect of acidic urine on patient survival. A multivariate analysis showed that high T stage (T3-4) (hazard ratio (HR) 5.18, P<0.001), decreased renal function (estimated glomerular filtration rate <60 mL/min/1.73 m2) (HR 2.29, P=0.003), and low urine pH (≤5.5) (HR 1.69, P=0.05) were associated with shortened recurrence-free survival (RFS). Regarding the overall survival (OS), high T stage (T3-4) (HR 7.15, P<0.001) and low urine pH (≤5.5) (HR 2.66, P=0.029) were significantly associated with shortened survival. A Kaplan–Meier analysis demonstrated that the acidic urine group showed shorter RFS (P=0.04) and OS (P=0.028) than the other groups. Conclusions Acidic urine was independently associated with reduced RFS and OS in patients with bladder cancer undergoing radical cystectomy. Acidic urine contributing to an acidic tumor environment may promote aggressive behavior in bladder cancer.